2012
DOI: 10.1111/j.1751-2980.2012.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the parvovirus H‐1 non‐structural protein NS1 on the tumorigenicity of human gastric cancer cells

Abstract: OBJECTIVE:  To investigate the in vivo oncosuppressive effect of the non‐structural protein NS1 of parvovirus H‐1 on human gastric cancer cell lines. METHODS:  Recombinant plasmid pcDNA3.1‐NS1 containing the complete NS1 gene of parvovirus H‐1 was constructed and characterized by restriction enzyme digestion and sequence analysis. The human gastric cancer cell lines MKN28, SGC7901 and MKN45 were stably transfected with empty or recombinant plasmids. NS1 gene transcription and protein expression in the latter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…13,14 H-1 virus is considered to be oncotropic, efficiently infecting human tumor cells such as melanoma, 15 hepatoma 16 and glioblastoma, 17 as well as cancerous colon and gastric tissues. 18,19 Kilham rat virus (KRV), belonging to the same Parvoviridae family as the H-1 virus, replicates in its natural host rodent cells. 20 Surprisingly, KRV induces autoimmune type I diabetes in diabetesresistant biobreeding rats.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 H-1 virus is considered to be oncotropic, efficiently infecting human tumor cells such as melanoma, 15 hepatoma 16 and glioblastoma, 17 as well as cancerous colon and gastric tissues. 18,19 Kilham rat virus (KRV), belonging to the same Parvoviridae family as the H-1 virus, replicates in its natural host rodent cells. 20 Surprisingly, KRV induces autoimmune type I diabetes in diabetesresistant biobreeding rats.…”
Section: Introductionmentioning
confidence: 99%
“… Gastric carcinoma H-1PV-induced killing of human gastric cancer cells was found to follow the up- or downregulation of the expression of a number of cellular genes [ 97 ]. Recombinant NS1 expression was also shown to reduce the tumorigenic potential of poorly differentiated gastric cancer cells implanted in nude mice, providing evidence that this viral protein interferes with the growth of these cells [ 98 ]. These studies warrant further testing of the antineoplastic effects of H-1PV on gastric tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as NS1 cytotoxic functions are greatly dependent on PDK1/PKC pathway, and the fact that this pathway is activated in most of the tumors, suggest that NS1 should preferentially target cancer cells. Indeed, NS1 has been shown to kill gastric tumor cells specifically in vitro as well as in the xenograft mouse model without causing any adverse effects on normal cells [57,58]. We also have demonstrated that NS1 could regress the chemically induced skin tumor in a rat tumor model [90].…”
Section: Parvovirus Ns1mentioning
confidence: 61%
“…The H-1PV NS1 expression seems to cause G2 arrest through up-regulation of p130 and p107 proteins, which are involved in maintaining G2 arrest by binding to an E2F family of transcription factors [17]. However, a G1 phase arrest, through the accumulation of p21 cip1 , has also been observed in gastric cancer cells where NS1 expression suppresses the growth of the tumor cells [57,58].…”
Section: Ns1 Of Rat Parvovirus H-1pv (H-1pv Ns1)mentioning
confidence: 99%